(untitled) (The Pakistan Development Review, 2015)
The primary focus of economics is to allocate resources in order to achieve the well-being of humans. Wellbeing has many dimensions, ranging from the level of mere subsistence to the equality of opportunities to accumulate, and to safeguard life and wealth. Poverty, thus, is one of the parameters for measuring the welfare of society in general. Given this importance, the Millennium Development Goals aim at halving the world poverty by 2015. Many organisations in the world set poverty eradication as one of their key objectives. Likewise, poverty reduction has got a central place in the international politics. Accordingly, each country including Pakistan has launched programmes for the alleviation of this great menace. The election manifesto of all the mainstream political parties in Pakistan includes poverty alleviation as one of their main goals. Additionally, poverty alleviation is one of the major subjects of talks in electronic media and in the editorials of newspapers, both at the national and at the international level. Nevertheless, poverty is still a major problem of humanity across the globe.